Supported silver nanoparticles over alginate-modified magnetic nanoparticles: Synthesis, characterization and treat the human lung carcinoma - Huang, Jing; Guo, Jiquan; Zhu, Jiaxin; Zou, Xiaoling (Journal of Saudi Chemical Society, 2022)
This article displays synthesis of Silver nanoparticles (Ag NPs) decorated on sodium alginate covered magnetite (Fe3O4/Alg-Ag NPs) nanocomposite. Sodium alginate shell as a natural anionic polysaccharide on Fe3O4 microparticles core acted as a stabilizing agent for the reduction of Ag(I) ions into Ag NPs. The structural features of the synthesized nanocomposite were investigated by fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), field emission scanning electron microscopes (FE-SEM), transmission electron microscopes (TEM), energy-dispersive X-ray spectroscopy (EDX) and vibrating-sample magnetometer (VSM) studies and inductively coupled plasma-optical emission spectroscopy (ICP-OES). 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay was used on common lung cancer cell lines i.e., NCI-H1975, NCI-H1563, and NCI-H1299 to survey the cytotoxicity and anti-lung cancer effects of the synthesized nanocomposite. The synthesized nanocomposite had very low cell viability and high anti-lung cancer activities dose-dependently against NCI-H1975, NCI-H1563, and NCI-H1299 cell lines without any cytotoxicity on the normal cell line (Human umbilical vein endothelial cells (HUVECs)). To determine the antioxidant properties of the synthesized nanocomposite, the 2,2-diphenyl-1-picrylhydrazyl (DPPH) test was used in the presence of butylated hydroxytoluene as the positive control. The synthesized nanocomposite inhibited half of the DPPH molecules in the concentration of 194 µg/mL. Maybe significant anti-human lung cancer potentials of the synthesized nanocomposite against common human lung cancer cell lines are linked to their antioxidant activities.